Evidence-based psychological practices in clinical psychologists from the Dominican Republic - Carlos Hernández; Alexis Lorenzo Ruiz (Medisur)
Foundation: Evidence-based psychological practices are the combination of the best available scientific research that takes into account clinical experience in the context of the patient, the culture and preferences of the patient. Objective: To determine the current state of evidence-based psychological practices in the Dominican Republic. Methods: Descriptive cross-sectional research, for which a probabilistic sample of 235 clinical psychologists working in private practice and in state hospitals was selected. The data were obtained with the Scale for an Evidence-Based Professional Practice. Results: It was found that the Scale for an Evidence-Based Professional Practice has adequate psychometric properties. 57 % of the clinical psychologists surveyed reported that they have received training to work with the scale; There were no significant differences between academic degree, length of practice, type of service provided (public or private) and knowledge, attitudes and behaviours of the clinical psychologists surveyed. However, training on the scale does influence knowledge, attitudes and behaviours towards evidence-based psychological practices. Conclusions: Training on the Scale for Evidence-Based Professional Practice influences clinical psychologists; knowledge, attitudes and behaviours towards evidence-based psychological practices, but not academic degree, length of practice, type of service provided (private/public).